The Implementation of 3-2-1 Strategy in Teaching Reading through Online Learning - Putu Melia Dewi; Ratminingsih, Ni Made; Saputra, I Nyoman Pasek Hadi (English Department, Universitas Negeri Surabaya, 2022)
This study aimed to investigate the effect of the implementation of 3-2-1 strategy in teaching reading through online learning towards the eighth-grade students’ reading comprehension of SMP Negeri 4 Busungbiu. This study was an experimental research with Pretest-Posttest Control Group Design. Two classes of the eighth-grade students in SMP Negeri 4 Busungbiu were selected as the sample of the study through cluster random sampling technique. Class VIII C was the experimental group which was taught reading through online learning by using 3-2-1 strategy, while class VIII A was the control group which was taught by using the conventional method. The pre-test and post-test data obtained in this study were analyzed descriptively and inferentially using SPSS 23.0. The result of the data analysis showed that the students in the experimental group performed better than the students in the control group after being given treatment. It was proven by the result of the descriptive analysis that showed the mean score of the experimental group (81.29) was higher than the mean score of the control group (69.81) in the post-test. Furthermore, the result of the independent sample t-test showed that the p-value of pre-test was 0.535 (> α = 0.05) and the p-value of post-test was 0.000 (< α = 0.05). Thus, it can be concluded that the implementation of 3-2-1 strategy gave a significant effect on the eighth-grade students’ reading comprehension achievement of SMP Negeri 4 Busungbiu.